An experimental study on the social trust and cooperation of North Korean refugees - Seo-Young Cho (Philipps-University Marburg, School of Business and Economics, 2019)
Many of North Korean refugees in South Korea struggle to reconcile their different identities of: being a Korean who shares ethnicity with South Koreans vs. being a North Korean who fled from an estranged neighboring country. This paper shows that emphasizing the Korean unity can help their integration in South Korea, despite considerable differences caused by seven-decade long separation between the North and the South. The results of a behavioral experiment with 130 North Korean refugees conducted in this study suggest that the unified Korean identity stimulates the refugees' social trust with South Koreans, cooperation in South Korea, and their self-confidence.
Keywords: D91; J15; 330; North Korean Refugees; Identity; Social Trust; Cooperation; Confidence; Integration